MO457PREVALENCE OF NON-ALCOHOLIC FATTY LIVER DISEASE IN PATIENTS WITH CHRONIC KIDNEY DISEASE: A CASE-CONTROL STUDY. (29th May 2021) - Adrian, Therese; Hornum, Mads; Soerensen, Ida Maria Hjelm; Freese Ballegaard, Ellen Linnea; Bro, Susanne; Kühl, Joergen Tobias; Sigvardsen, Per Ejlstrup; Fuchs, Andreas; Kofoed, Klaus F; Knop, Filip K; Feldt-Rasmussen, Bo
Abstract: Background and Aims: Non-alcoholic fatty liver disease (NAFLD) is the most common liver disease and is characterised by hepatic accumulation of lipids. NAFLD represents a wide spectrum ranging from mild steatosis over non-alcoholic steatohepatitis with and without fibrosis to overt cirrhosis. Patients with NAFLD have a high risk of developing cardiovascular disease and chronic kidney disease (CKD). So far, there is scarce evidence of the prevalence of NAFLD among patients with CKD. The aim of this study was to investigate the prevalence of moderate to severe steatosis in a cohort with patients with different stages of CKD not on dialysis. Method: A total of 291 patients from the Copenhagen Chronic Kidney Disease Study were included. For comparison, 866 participants with normal kidney function from the Copenhagen General Population Study were identified as controls. Blood samples, clinical demographics, information about smoking and alcohol were collected. Hepatic liver fat fraction was evaluated in all participants by computed tomography (CT). Liver attenuation density <48 Hounsfield Units was used as cut-off value for moderate to severe steatosis corresponding to 10% liver fat after transformation of the CT attenuation. Results: The prevalence of moderate to severe steatosis was 7.9% and 10.7% among patients with CKD and controls, respectively. Data of the continuous Hounsfield Units showed lower values among patients with CKD compared with the control group. No significant association between liver fat fraction and CKD stage was found. Pooled data from both cohorts showed that adjusted odds ratios (OR) for steatosis were strongly significant among persons with diabetes (OR 3.1, 95% confidence interval (CI) 1.6-5.9), overweight (OR 14.8, 95% CI 4.6-47.9) and obesity (OR 42.0, 95% CI 12.9-136.6), respectively. Conclusion: In the present cohort of 291 patients with CKD, kidney function was not associated with the prevalence of hepatic steatosis as assessed by CT scan.